Artificial intelligence, Pendorong atau Penghambat Minat Belajar Generasi Z: Tinjauan Literatur - qoyim, ismaa ul (Maliki Interdisciplinary Journal, 2026)
This literature review analyzes the impact of Artificial Intelligence (AI) on Generation Z’s learning interest, given AI’s significant role in their education and daily lives. The study adopts a literature review methodology, examining indexed international journal articles published within the last five years from databases such as Google Scholar, Scopus, and Web of Science. The selected literature is reviewed to identify patterns, trends, and knowledge gaps concerning AI’s influence on Gen Z’s learning interest. The findings highlight a dual impact of AI: on the one hand, it enhances learning efficiency and personalization, facilitates information access, and strengthens digital competence; on the other hand, it poses risks of over-dependence, reduced critical thinking, diminished social interaction, and potential ethical and psychosocial challenges. The review concludes that AI can positively foster Gen Z’s learning interest if integrated thoughtfully. Key recommendations include positioning AI as a supportive learning tool rather than a substitute for cognitive processes, reinforcing the role of teachers and humanistic interaction, implementing strict ethical regulations and policies, and promoting digital literacy and critical awareness.